Activated carbons from passion fruit shells in adsorption of multimetal wastewater - de Paula Ramos, Bianca; Perez, Isadora Dias; Paiano, Murillo Silva [UNESP]; Vieira, Melissa Gurgel Adeodato; Boina, Rosane Freire [UNESP] (Springer Nature, 2022)
This work aims to use a solid agro-industrial residue (passion fruit shells—PF) to manufacture different activated carbons (ACs) capable to retain Cr3+, Cu2+, and Ni2+ on synthetic wastewater. The PF was carbonized and chemically activated with three precursors, giving rise to three ACs: phosphoric acid (ACH2PO4), sodium acetate (ACC2H3NaO2), and potassium hydroxide (ACKOH). The ACs were characterized by SEM, ASAP, FTIR, and pH-PZC. The adsorption phenomena were studied by kinetic and isotherm models. The efficiency of the process was investigated in mono- and multimetallic solution with two-way ANOVA and Tukey test at 95% confidence interval. The physical-chemical modifications in the solid increased the surface area, the porosity, and the heterogeneity. The phenomena had a better fit to the pseudo-second-order kinetic model and to the Freundlich isotherm model. Analyzing the interaction between the ACs and the composition of the solutions, the selectivity of the solid and the competition for activated sites were verified. Efficiencies higher than 95% were obtained for Ni2+, 80% for Cu2+, and 70% for Cr3+. The viability of the process in mono- and multimetallic solutions opens the possibility of integrated management of metallic wastewater and agro-industrial residues.
Keywords: Activated charcoal; Biochar; Metal ions; Multicomponent solution; Passiflora edulis; Wastewater treatment